Integrasi Nilai-Nilai Islam dalam Ritual Rofaerwar: Pelestarian Budaya Lokal di Desa Lonthoir, Kepulauan Banda - Man Arfa, Arman; Lasaiba, Djamila (JENDELA PENGETAHUAN, 2025)
The Rofaerwar ritual or sacred well cleansing is a cultural tradition held once every ten years by the people of Lonthoir Village, symbolizing reverence for ancestors and the preservation of a sacred water source. This practice represents a generational integration of Islamic values with local customs. The aim of this study is to explore the ritual’s implementation, symbolic meanings, and the role of Islamic principles embedded within. A descriptive qualitative method with an ethnographic approach was employed. Findings indicate that Rofaerwar is not merely a physical act but a spiritual and communal event imbued with meaning. Elements such as prayer, deliberation, and the use of Islamic symbols like kain gaja and karaso strengthen the ritual’s religious depth. The study demonstrates that Islamic faith and tradition coexist harmoniously without conflicting values. The implication is that the sustainability of such rituals requires active involvement of traditional leaders, youth, and religious institutions as part of a cultural development strategy. It is recommended to enhance local wisdom-based education to preserve core values amidst modern shifts.